Blockchain and IoT: Opportunities and Challenges - Mardiansyah, Viddi (International Journal of Psychosocial Rehabilitation, 2020)
Blockchain innovation has been changing the budgetary business and has made another cryptoeconomy in the most recent decade. The fundamental ideas, for example, decentralized trusting and distributing ledgerss are a pledge for dispersed and substantial-scale IoT (Internet of Things) implementation. In any case, the utilizations of blockchain digital forms of money in this space are rare in light of a lack of understanding and inborn design difficulties. In this paper, we depict the open doors for implementation utilizing blockchain and IoT and inspect the difficulties engaged with architecting Blockchain-based IoT applications (Abstract)